Assessment of physiological upper eyelid laxity - Broussard, M.; Leveziel, N.; Lii, M.; Tonnerre, D.; Flausse, R. (Journal francais d'ophtalmologie, 2019)
To evaluate overall upper eyelid laxity according to age and sleep position. This single-center prospective study was conducted on healthy subjects between 20 and 89 years of age and was approved by the institutional review board and the ethics committee. Data collected were age, sex, weight and height, ophthalmological history, general history (diabetes, hypertension, smoking) and preferred sleep position (lateral, ventral, dorsal decubitus or no preference). Overall upper eyelid laxity was measured using the McNab technique. In total, 280 patients were included in the study – 40 per 10-year age bracket. Mean overall right eyelid laxity was measured at 5.35mm (5.38mm on the left) between 20 and 29 years old and 8.28mm (8.43mm on the left) between 80 and 89 years old. 161 patients slept in a lateral decubitus position. Median overall upper eyelid laxity for the sleep side was 8mm vs. 7mm for the non-sleep side. Overall upper eyelid laxity increased significantly with age (P<0.001) and compared to the contralateral side (P<0.001). Overall upper eyelid hyperlaxity can be defined as a measurement (by the McNab technique) greater than: 7mm between 20 and 29 years, 8mm between 30 and 39 years, 9mm between 40 and 69 years and 10mm between 70 and 89 years. This study provides new data on normal eyelid laxity in the general population according to age and sleep position. Évaluer la laxité palpébrale supérieure par tranche d’âge et analyser son évolution afin de pouvoir définir avec plus d’objectivité l’hyperlaxité palpébrale décrite dans les différents syndromes et d’étudier cette dernière en fonction de la position préférentielle de sommeil. Il s’agit d’une étude prospective, monocentrique réalisée chez des sujets sains entre 20 et 89 ans. La mesure de la laxité palpébrale supérieure a été réalisée selon la technique de McNab. Les informations suivantes étaient recueillies : âge, sexe, poids et taille, antécédents ophtalmologiques et généraux (diabète, HTA, tabagisme) ainsi que la position préférentielle de sommeil (decubitus ventral, latéral, dorsal ou sans préférence). Au total, 280 sujets ont été inclus dans cette étude soit 40 par tranche de 10 ans. La laxité palpébrale supérieure moyenne était mesurée à 5,35mm à droite (contre 5,38mm à gauche) entre 20 et 29 ans et à 8,28mm à droite (contre 8,43mm à gauche) entre 80 et 89 ans. Au total, 161 patients dormaient en décubitus latéral. La moyenne de laxité palpébrale supérieure était de 8mm du côté préférentiel de sommeil et de 7mm pour le côté controlatéral. La laxité palpébrale supérieure augmentait significativement avec l’âge et la position préférentielle de sommeil. L’hyperlaxité palpébrale supérieure pourrait se définir par des valeurs supérieures à 7mm entre 20 et 29 ans, 8mm entre 30 et 39 ans, 9mm entre 40 et 69 ans et 10mm entre 70 et 89 ans. Cette étude fournit de nouvelles données sur la laxité physiologique en fonction de l’âge et du côté du sommeil.